2004
DOI: 10.1111/j.1442-2042.2003.00771.x
|View full text |Cite
|
Sign up to set email alerts
|

Metanephric Adenoma Treated with Laparoscopic Nephrectomy

Abstract: A 31-year-old-female presented with a left renal mass detected incidentally during an abdominal ultrasound examination. Computed tomography and angiography revealed a hypovascular solid tumor 4.5 cm in diameter at the middle portion of the left kidney. Laparoscopic left nephrectomy was performed and macroscopic examination of the specimen revealed encapsulated tumor with grayish yellow cut surface. Histological examination demonstrated that the tumor cells were small scant cytoplasms, containing round and regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…CT scan showed that the tumor was slight and gradually enhanced in each period, with a lower enhancement degree than that of the adjacent normal kidney tissue. It is debatable whether to use needle biopsy for preoperative diagnosis (Ebine et al 2004 ). We did not perform preoperative biopsy because of the following two reasons: 1) additional risk of tumor spread and bleeding; and 2) the surgical approach or planning was the same for either renal cell carcinoma or MA.…”
Section: Discussionmentioning
confidence: 99%
“…CT scan showed that the tumor was slight and gradually enhanced in each period, with a lower enhancement degree than that of the adjacent normal kidney tissue. It is debatable whether to use needle biopsy for preoperative diagnosis (Ebine et al 2004 ). We did not perform preoperative biopsy because of the following two reasons: 1) additional risk of tumor spread and bleeding; and 2) the surgical approach or planning was the same for either renal cell carcinoma or MA.…”
Section: Discussionmentioning
confidence: 99%
“…Most of our patients underwent nephrectomy mainly because of the difficult preoperative differentiation of their lesions from malignant renal tumours. Because imaging is unable to exclude renal cell carcinoma, centrally located or anatomically complex masses should be treated by radical nephrectomy [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our two patients were also treated with partial nephrectomy, procedure with better renal function preservation, without compromising the patient’s survival. Further advance in reducing patient morbidity may be achieved by laparoscopic nephrectomy as reported by Ebine et al11 in 2004 for MA treatment in a 31 years old female patient with a left renal mass of 4.5 cm detected incidentally during an abdominal ultrasound examination. Three years latter, Kumar et al12 reported a laparoscopic partial nephrectomy as treatment for MA in a 47‐year‐old patient.…”
Section: Discussionmentioning
confidence: 99%